Tritium on ice : the dangerous new alliance of nuclear weapons and nuclear power - Bergeron, Kenneth D. (MIT Press, 2002)
The dangers of a United States government plan to abandon its fifty-year policy of keeping civilian and military uses of nuclear technology separate. In December 1998, Energy Secretary Bill Richardson announced that the U.S. planned to begin producing tritium for its nuclear weapons in commercial nuclear power plants. This decision overturned a fifty-year policy of keeping civilian and military nuclear production processes separate. Tritium, a radioactive form of hydrogen, is needed to turn A-bombs into H-bombs, and the commercial nuclear power plants that are to be modified to produce tritium are called ice condensers. This book provides an insider's perspective on how Richardson's decision came about, and why it is dangerous. Kenneth Bergeron shows that the new policy is unwise not only because it undermines the U.S. commitment to curb nuclear weapons proliferation but also because it will exacerbate serious safety problems at these commercial power facilities, which are operated by the Tennessee Valley Authority and are among the most marginal in the United States. The Nuclear Regulatory Commission's review of the TVA's request to modify its plants for the new nuclear weapons mission should attract significant attention and opposition. Tritium on Ice is part expose, part history, part science for the lay reader, and part political science. Bergeron's discussion of how the issues of nuclear weapons proliferation and nuclear reactor safety have become intertwined illuminates larger issues about how the federal government does or does not manage technology in the interests of its citizens and calls into question the integrity of government-funded safety assessments in a deregulated economy.